2018
DOI: 10.1002/tesq.472
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Disciplinary Linguistic Knowledge With English Learners and Their Teachers: Applying Systemic Functional Linguistics Concepts Through Design‐Based Research

Abstract: A focus on how language varies in its forms and meanings can help English learners (ELs) in K-12 classrooms engage in disciplinary discourses that enable them to learn both language and content. Systemic functional linguistics (SFL) offers promising ways of talking about language in support of disciplinary learning. SFL's meaningbased metalanguage offers analytical tools for making sense of text, but its description of complex systems in language is not readily accessible to teachers and students. This article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…However, there is also a concern for instrumental approaches to reading strategies, which may limit opportunities for meaningful engagements with texts (Thavenius, 2017;Walldén, 2019b). Similarly, studies have highlighted misalignments between the modelling of metalinguistic knowledge and engagement with subject content (Moore, Schleppegrell & Palincsar, 2018;Walldén, 2019c).…”
Section: Supporting L2 Learners By Sharing Metaknowledgementioning
confidence: 99%
“…However, there is also a concern for instrumental approaches to reading strategies, which may limit opportunities for meaningful engagements with texts (Thavenius, 2017;Walldén, 2019b). Similarly, studies have highlighted misalignments between the modelling of metalinguistic knowledge and engagement with subject content (Moore, Schleppegrell & Palincsar, 2018;Walldén, 2019c).…”
Section: Supporting L2 Learners By Sharing Metaknowledgementioning
confidence: 99%
“…The focus was on understanding how such supports could be integrated while maintaining the integrity of the units’ engineering goals. We chose design-based research because it offers analytic methods to systematically operationalize the development of instructional theories over time and within the context of classroom practice (Anderson & Shattuck, 2012; DiSessa & Cobb, 2004; Moore et al, 2018). Our research and instructional team members’ multiple perspectives stemming from expertise in literacy, engineering, and classroom teaching were integral to the research process.…”
Section: The Studymentioning
confidence: 99%
“…During teaching, we used tools from participatory action research described above to inform instruction. After teaching, we reviewed data to identify and analyze relevant episodes (Moore et al, 2018) in the classroom talk where language support and engineering reasoning were simultaneously visible. We conducted discourse analysis of these episodes, followed by analysis of students’ written explanations using rubrics informed by SFL (Brisk, 2015; Hodgson-Drysdale, 2014) and mechanistic reasoning (Russ et al, 2008).…”
Section: The Studymentioning
confidence: 99%
“…Relevant research, especially in the traditional classroom, has demonstrated the usefulness of SFL to help students power through challenges in the writing classrooms following the reading to learn cycle (i.e., reading sample texts and then guiding students in understanding meaning-making and constructing their writing) [13], [17], [18], [19]. For example, Moore, Schleppegrel, and Palincsar focused on elementary English-as-a-second-language (ESL) students in the US who were exposed to the teaching of narratives from a functional linguistic perspective [20]. Over two years, the students were able to identify the interrelationships between linguistic resources and meanings in sample narrative texts, such as the identification of processes at the ideational level and appraisal resources at the interpersonal level.…”
Section: Systemic Functional Linguistics As a Potentially Helpful Framework For Mobile-assisted Writing Instructionmentioning
confidence: 99%